Canadian radiology workforce demographics: Results from a national survey - Elizabeth Hillier; Carol S. Hodgson; Kiana Lebel; Lucy B. Spalluto; Isabelle Trop; Wan Wan Yap; Tracey Hillier; Kathryn E. Darras; Sonali Sharma; Charlotte J. Yong-Hing (Heliyon, 2023)
Rationale and objective: Demographic data collected about Canadian radiologists and trainees has been limited primarily to binary gender and geographic location. The purpose of this study was to investigate: (1) demographic characteristics of Canadian radiologists and trainees; (2) types of diversity important to radiologists; (3) relationship of radiologist demographics to practice characteristics; and (4) relationship of radiologist demographics to years in practice, (YIP). Materials and methods: French and English surveys were distributed via email through radiology associations and social media. Frequency counts of demographic variables were calculated, and chi-square and Fisher's Exact tests were performed to explore the relationships between demographic characteristics and role. Results: 611 individuals responded to the survey. 573 respondents were included in the analysis. 454 (78.8%) were practicing radiologists and 119 (20.7%) were residents/fellows. Half identified as women (50.4%). English was the primary language for most respondents. There was an association between role and sexual orientation (p = 0.02), visible minority (χ2 = 4.79, p < 0.05), religion (χ2 = 4.11, p < 0.05), and having children (χ2 = 136.65, p < 0.05). For radiologists, being a visible minority (χ2 = 11.59, p < 0.05) and age (χ2 = 56.3, p < 0.05) were associated with academic rank while gender (χ2 = 3.83, p < 0.05) and age (χ2 = 13.74, p < 0.05) were related to part-/full-time status. Less women, visible minorities, and women with children had been in practice for long. Discussion: This study represents a comprehensive analysis of Canadian radiology demographics. Results suggest there is increasing diversity among trainees; however, significant demographic underrepresentation compared to the diversity of Canada exists.